Specificity of mannan antigen and anti‐mannan antibody screening in patients with haematological malignancies at risk for fungal infection. Issue 6 (25th February 2016) - Duettmann, Wiebke; Koidl, Christoph; Krause, Robert; Lackner, Gertrude; Woelfler, Albert; Hoenigl, Martin
Summary: Combination of mannan antigen and anti‐mannan antibody (Mn/A‐Mn) testing has been reported a useful and specific strategy for diagnosis of invasive Candida infections (ICIs). We evaluated Mn/A‐Mn as a screening tool in patients with haematological malignancies. This clinical prospective study was performed at the Division of Hematology, Medical University Graz, Austria between July and December 2012. Patients at risk for fungal infection were included into the study and twice weekly screened by Mn/A‐Mn testing, yielding 650 samples. Of overall 67 patients 66 had no evidence for ICI. From those, 153/640 serum samples (23.9%) were positive for mannan Ab, and nine (1.4%) for Ag. Most false positive Ab results were observed among 375 samples from patients without haematopoietic stem cell transplantation (34.9% resulted positive). Combined specificity of Mn/A‐Mn was 74.8%. Of 10 samples obtained in the single patient with candidemia, five were positive for mannan Ag (from the day of diagnosis up to 40 days after detection of candidemia) and none for Ab. In conclusion, mannan Ab screening yielded a high number of false positive results. While mannan Ag was found to be highly specific and may have potential for diagnostic driven testing, mannan Ab testing cannot be recommended based on our study results.